2011
DOI: 10.1002/chem.201003402
|View full text |Cite
|
Sign up to set email alerts
|

Combining Glycomimetic and Multivalent Strategies toward Designing Potent Bacterial Lectin Inhibitors

Abstract: As part of ongoing activities toward the design of potent and selective ligands against galactoside-binding proteins from animal, bacterial, and plant lectins, a systematic investigation involving the synthesis and binding evaluations of a series of original β-C-galactopyranoside mimetics is described. The multivalent presentation of partly optimized candidates on various dendritic scaffolds through Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAc) has also been achieved. Biophysical investigations based on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 96 publications
3
71
0
Order By: Relevance
“…Zemplén deprotection (NaOMe, MeOH) afforded 5 in 94% yield. Synthesis of the related homolog 9 , prepared in 74% overall yield from known 6 [17] by an analogous click chemistry, is also described in Scheme 1. To this end, trichloride 1 was treated as above with 3-azido-1-propanamine to provide 6 in 87% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zemplén deprotection (NaOMe, MeOH) afforded 5 in 94% yield. Synthesis of the related homolog 9 , prepared in 74% overall yield from known 6 [17] by an analogous click chemistry, is also described in Scheme 1. To this end, trichloride 1 was treated as above with 3-azido-1-propanamine to provide 6 in 87% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Among the diverse strategies leading to efficient ligands, glycopolymers [1,57], glycodendrimers [714], and sugar rods [1516] have retained most attention. An additional approach that has gained keen interest resides in the modifications of both the aglycon [1719] and substituent residues [2022] of the targeted sugar moieties through extensive studies of quantitative structure–activity relationships (QSARs). In most of the studies related to aglycon modifications, it was concluded that aromatic glycosides possessed improved binding properties due to the ubiquitous presence of aromatic amino acids in the cognate binding sites [2325].…”
Section: Introductionmentioning
confidence: 99%
“…(Chabre et al, 2011) Triphenylamine Glucose TOF Star-shaped glycosylated conjugated oligomer for twophoton fluorescence imaging Trivinyl benzene Sulfonated-GlcNAc TOF Click chemistry. Synthesis and observation of a reduction in nanofiber formation Poly-( -amino esters) TOF Synthesis of nanoparticles for sustained drug delivery across the blood-brain barrier (Gil et al, 2012) Sucrose Peptides TOF (sinapinic)…”
Section: R-tof (Thap)mentioning
confidence: 99%
“…It has been shown that solutions of galactose and fucose which are capable of bounding to LecA and LecB, respectively, have a therapeutic potential against P. aeruginosa pneumonia in a mouse model and in patients with cystic fibrosis. [9] Recently it has been investigated that peptide glycomimetics have high binding affinity to both LecA and LecB, and prevent their toxic activity. [10] LecA (also called PA-IL) is a tetrameric cytotoxic lectin consisting of four subunits of 121 amino acids (12.75 kDa) each with specificity to α-D-galactose and, preferentially, to binding to Gal-α-(1,4)-Gal, containing globotriacylceramide Gb3 sphingolipid.…”
Section: Glycodendrimers As Potential Therapeutic Agentsmentioning
confidence: 99%